1998
DOI: 10.1159/000024021
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Soluble Interleukin–2 Receptor at Acute Asthma Exacerbation: Relationship with Severity of Exacerbation and Bronchodilator Response

Abstract: Background: T lymphocytes play a central role in the regulation of airway inflammation in asthma, and T cell activation appears to be a characteristic feature of acute asthma. It is not clear, however, whether this is proportional to the severity of acute asthma and is directly related to airway inflammation relevant to airflow obstruction during acute asthma. It is presumed that the extent to which bronchoconstriction or inflammation contributes to airflow obstruction in acute asthma may determine responsiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…We took great care with the collecting and processing of blood samples. Our findings expand on the results of previous studies [24, 46]by showing not only that serum levels of sIL-2R at acute exacerbation were significantly higher than the internal control, but also that the levels correlated positively with the severity of bronchoconstriction. However, levels of serum sIL-2R did not correlate significantly with the degree of responsiveness to bronchodilator therapy at acute exacerbation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We took great care with the collecting and processing of blood samples. Our findings expand on the results of previous studies [24, 46]by showing not only that serum levels of sIL-2R at acute exacerbation were significantly higher than the internal control, but also that the levels correlated positively with the severity of bronchoconstriction. However, levels of serum sIL-2R did not correlate significantly with the degree of responsiveness to bronchodilator therapy at acute exacerbation.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have demonstrated that serum levels of sIL-2R are elevated in patients with asthma [15, 44, 45, 46]. It is not clear, however, whether the levels increase further during acute asthma [24, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Matsumoto et al [6] also have shown that serum sIL-2R was elevated in asthmatics compared with normal control subjects. Although the comparison of sIL-2R between asthmatic and normal subjects was not a scope of our study [1], the increase in serum sIL-2R levels in asthmatic subjects compared with normal subjects may be one evidence that T cell activation is present in asthmatics.…”
Section: Dear Sirmentioning
confidence: 94%